New Dilemmas and New Directions in South Africa After Apartheid - Anrys, Stefaan; Chan, David; Sachs, Albie (Afrika Focus, 2019)
On 3 October 2016, Sachs, who collects honorary doctorates and other titles as if they were panini stickers, visited Ghent University for the third Mandela Lecture organised by the Africa Platform of the Ghent University Association, and moderated by Prof. Eva Brems. This interview was conducted on that occasion. ‘Since the attempt on my life, I see everything as rose-tinted’, laughs the man who sur- vived an attack, abolished the death penalty and was close to the ANC leadership. ‘If I were to become pessimistic about South Africa, people would really get scared, they’d say: Oh, even Albie doesn’t like it anymore ’(laughs). In 1988 Albie Sachs was viciously attacked, losing his right arm and the sight of one eye. He was living in exile in Mozambique at the time, as South Africa suffered under the Apartheid regime. Sachs was one of the prominent freedom fighters, but survived the assassination attempt and eventually became an important member of the ANC, one of the many authors of the Constitution of the new South Africa. He was also invited by Mandela to sit on the Constitutional Court, which abolished the death penalty and forced Parliament to legalise LGBT marriage. In Ghent, the now 81-year-old freedom fighter nuances the pessimistic news coming out of South Africa. ‘A lot is going wrong in South Africa. But what gives me hope is that people can speak their minds. Our democracy works. Our institutions work, and not just the courts and tribunals. Recently we had elections, and they were free and fair. And yes, the ANC lost the elections. But that is in fact the best evidence that our democracy works.’